Effect of educational and support interventions on long-term breastfeeding rates in primiparous women: a systematic review and meta-analysis. (September 2017) - Meedya, Shahla; Fernandez, Ritin; Fahy, Kathleen
EXECUTIVE SUMMARY: Background: Long-term breastfeeding, including exclusive breastfeeding for six months and continuation of breastfeeding with complementary food until two years of age, has been recommended by the World Health Organization. However, despite the clear benefits of long-term breastfeeding (six months and beyond), the rates of breastfeeding still continue to remain low. Although there are some individual interventional studies that aimed to increase prolonged breastfeeding rates among both multiparous and primiparous women, there is no systematic review or meta-analysis to examine the effectiveness of those interventions among primiparous women who had no previous breastfeeding experience. Objectives: The aim of this review was to identify the effects of professional educational and support interventions on breastfeeding rates at six months and up to two years postpartum compared to the standard care among primiparous women. Inclusion criteria Types of participants : Studies that included primiparous women aged 18 and over who intended to breastfeed. Types of intervention(s): Studies that investigated the effect of educational and support interventions provided by health professionals during the antenatal, postnatal period or both. Types of studies: Randomized controlled trials. Outcomes: Studies with reported breastfeeding rates at six months or up to two years postpartum. Search strategy: A three-step search strategy was utilized in this review. The search was conducted in Cochrane, MEDLINE and CINAHL databases. Only trials that met the inclusion criteria and published in English were considered for this review. Databases were searched from their commencement year to May 2016. Methodological quality: Two independent reviewers selected the papers using the standardized critical appraisal tool from the Joanna Briggs Institute. Data extraction and data synthesis: Data was extracted using the standardized Joanna Briggs Institute data extraction instrument. Quantitative data were, where possible, pooled in statistical meta-analysis using RevMan v5.3 (Copenhagen: The Nordic Cochrane Centre, Cochrane). In the absence of trials comparing the same outcomes, meta-analysis could not be performed; the findings have therefore been presented in a narrative form, including tables and figures to aid in data presentation where appropriate. Results: Ten randomized controlled trials were included in this review. Interventions with only one antenatal or postnatal component were not effective in increasing breastfeeding rates at six months. However, based on one trial, an intervention that included antenatal education and support in combination with postnatal education and support doubled the rate of breastfeeding at six months among primiparous women randomized to the intervention group compared to the control group ( p = 0.28). Conclusion: Despite the good methodological quality of the trials, due to the heterogeneity of the interventions and outcome measures (types of breastfeeding) it was not possible to identify any specific effective intervention. However, based on a single trial, it appears that a combination of antenatal and postnatal education interventions may be useful in increasing breastfeeding rates at six months.